STRATEGI BERTAHAN HIDUP PEDAGANG JAMU TRADISIONAL DI PASAR KAHAYAN KOTA PALANGKA RAYA - Selfi Yunus; Saputra Adiwijaya; Atem Atem (Jurnal Ilmiah Sosiologi Agama (JISA), 2025)
This study aims to explore the survival strategies of traditional herbal medicine vendors in Kahayan Market, Palangkaraya City, in maintaining their businesses, using a descriptive qualitative approach. Data were obtained through in-depth interviews with five traditional herbal medicine vendors using purposive sampling techniques, observation, and literature study. This study uses James C. Scott's theory of survival strategies (survival mechanisms). The findings show that the survival strategies applied by traditional herbal medicine vendors include (1) tightening their belts (by saving on expenses, buying only basic necessities, managing their finances wisely, and saving money), (2) alternative means of subsistence (taking on side jobs, helping to clean other people's houses, such as sweeping or tidying up, participating in social gatherings as an emergency fund, and implementing sales strategies) (3) social networks (utilizing relationships with family, relatives, to obtain capital assistance and financial support)). Trades also face several challenges such as (1) high competition in the market, (2) customer instability, and (3) difficulty in obtaining raw materials.